2014
DOI: 10.1002/jsfa.6681
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of protein, lipid and mineral contents in common Norwegian seaweeds and evaluation of their potential as food and feed

Abstract: In total, the red alga P. palmata was regarded as the best alternative to cereals in food and feed. For several of the other species, single-component extraction for the ingredients market may be better than using the whole product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
205
9
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 280 publications
(286 citation statements)
references
References 46 publications
39
205
9
2
Order By: Relevance
“…Most species share a low lipid content on the one hand, while being rich in polysaccharides (both structural and storage, Dawczynski et al 2007) and minerals on the other (Mabeau and Fleurence 1993;Rupérez 2002;MacArtain et al 2007;Pereira 2011). Other nutritional properties, such as a relatively high protein content and high quality profiles of amino-acids (Fleurence 2004;Maehre et al 2014), lipids (Sánchez-Machado et al 2004) and minerals (Cofrades et al 2008;López-López et al 2009) are highly relevant towards food and feed applications. Positive effects of including seaweeds in feed meals have been reported for both, marine and terrestrial organisms (Soler-Vila et al 2009;Kandasamy et al 2012;Evans and Critchley 2014;Wilke et al 2015), and several feed products based on powdered dried seaweed are commercially available.…”
Section: Product Applications-industrial Perspectivesmentioning
confidence: 99%
“…Most species share a low lipid content on the one hand, while being rich in polysaccharides (both structural and storage, Dawczynski et al 2007) and minerals on the other (Mabeau and Fleurence 1993;Rupérez 2002;MacArtain et al 2007;Pereira 2011). Other nutritional properties, such as a relatively high protein content and high quality profiles of amino-acids (Fleurence 2004;Maehre et al 2014), lipids (Sánchez-Machado et al 2004) and minerals (Cofrades et al 2008;López-López et al 2009) are highly relevant towards food and feed applications. Positive effects of including seaweeds in feed meals have been reported for both, marine and terrestrial organisms (Soler-Vila et al 2009;Kandasamy et al 2012;Evans and Critchley 2014;Wilke et al 2015), and several feed products based on powdered dried seaweed are commercially available.…”
Section: Product Applications-industrial Perspectivesmentioning
confidence: 99%
“…In addition, being a very diverse group of plants, they are abundant in marine environments all over the world (Bolton 1994). In several studies, it has been shown that many seaweed species contain good quality protein in sufficient amounts to be used as biomass (substrate) for economically and environmentally justifiable large-scale protein (food) production (Kolb et al 2004;Maehre et al 2014;Taboada et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, seaweed biomass also has potential as a functional food ingredient: excessive sodium salts in processed foods, which often are associated with common health risks such as high blood pressure and cardiovascular diseases (Gibbs et al 2000), may be replaced by macroalgae rich in potassium salts (Hotchkiss 2009), resulting in healthier mineral profiles (Cofrades et al 2008, López-López et al 2009). In addition, nutritional properties such as high content in dietary fibres (Dawczynski et al 2007), protein and amino-acid profile (Fleurence 2004, Maehre et al 2014) and lipid profile (Sánchez-Machado et al 2004) are highly relevant for food applications.…”
Section: Introductionmentioning
confidence: 99%